A Generalized Distributed Energy Dispatch and Congestion Management Approach Applied to German and Japanese Grid Systems - Maximilian Kilthau; Toko Mannari; Tomo Tadokoro; Hiroyuki Hatta; Alexander Fay; Felix Gehlhoff (IEEE Access)
The growing penetration of renewable energy sources and the increasing number of electrical consumers at the low-voltage level present significant challenges for controlling the low-voltage grid. This paper addresses these challenges by proposing a decentralized approach to energy dispatch and grid congestion management. While the global energy transition is driven by the urgent need to address the climate crisis, much of the current research remains focused on national solutions. Furthermore, centralized approaches to energy transition and congestion management pose risks such as single points of failure and limited scalability. To overcome these limitations, this paper introduces a decentralized method applicable to both German and Japanese systems. The proposed method is validated using the Comprehensive Analysis Tool for Distribution System and Distributed Generation for power flow analysis, combined with a road traffic simulation to model Japanese charging behavior patterns. Simulation results demonstrate the approach’s generalizability across various systems, highlighting the distinct country-specific characteristics of Germany and Japan. Additionally, the decentralized approach’s applicability to both countries is demonstrated and discussed. Furthermore, the decentralized control strategy is tested in a laboratory setting, integrating DC loads and sources, back-to-back inverters, and three-phase energy distribution. The results confirm that the decentralized control method effectively transmits control signals to real systems and that the underlying mathematical models accurately reflect real-world scenarios.